Myanmar’s agrifood system: Historical development, recent shocks, future opportunities - Boughton, Duncan; Belton, Ben; Lambrecht, Isabel B.; Masias, Ian; Minten, Bart (International Food Policy Research Institute, 2024)
Myanmar has endured multiple crises in recent years — including COVID-19, global price instability, the 2021 coup, and widespread conflict — that have disrupted and even reversed a decade of economic development. Household welfare has declined severely, with more than 3 million people displaced and many more affected by high food price inflation and worsening diets. Yet Myanmar’s agrifood production and exports have proved surprisingly resilient.